From Latent Semantics to Spatial Hypertext - An Integrated Approach - Chen, Chaomei; Czerwinski, Mary (Hypertext '98, The Proceedings of the 9th ACM Conference on Hypertext and Hypermedia, 1998)
In this paper, we introduce an integrated approach to the development of spatial hypertext. This approach brings together several theories and techniques concerning semantic structures, and streamlines the transformation from implicit semantic structures to a semantic space rendered in virtual reality. Browsing and querying become natural, inherent, and compatible activities within the same semantic space. The overall design principle is based on the theory of cognitive maps. Techniques such as latent semantic indexing, Pathfinder network scaling, and virtual reality modelling are used in harmony. The value of this integrated approach is discussed based on initial results of a recent empirical study, which suggests that the spatial metaphor is intuitive and particularly useful when dealing with implicit information structures, or when a highly flexible and extensible virtual environment is required. Search strategies in association with the spatial hypertext and further work are also discussed.